2008
DOI: 10.1080/10550880802122687
|View full text |Cite
|
Sign up to set email alerts
|

Encouraging Physicians to Screen for and Intervene in Substance Use Disorders: Obstacles and Strategies for Change

Abstract: The scientific literature was reviewed to identify obstacles and effective ways to improve primary care physician screening, interventions, and management of patient substance use disorders (SUDs). Major obstacles identified are physician lack of skills and self-efficacy in patient counseling, inadequate training at all levels of medical education, and lack of reimbursement and other health care systems support for services to patients. Physician abuse of drugs does not appear to be a major obstacle. Physician… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 112 publications
0
34
0
Order By: Relevance
“…This is a public health issue that must not be underestimated, and medical training on substance abuse needs to be strengthened. For instance, substance use content may be integrated within training using didactic lectures, case-based learning, internships and objective, structured, clinical examination (21). Furthermore, medical students should have access to safe and confidential psychological support, although more-focused investigation of this aspect is required to support this conclusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a public health issue that must not be underestimated, and medical training on substance abuse needs to be strengthened. For instance, substance use content may be integrated within training using didactic lectures, case-based learning, internships and objective, structured, clinical examination (21). Furthermore, medical students should have access to safe and confidential psychological support, although more-focused investigation of this aspect is required to support this conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have highlighted the role of medical education in ensuring that doctors become competent in managing patients with substance abuse. However, some studies have shown that the integration of training in substance abuse management into medical curricula is suboptimal (19,20), leaving physicians unprepared to address these issues in patient care (21). Therefore, measuring students' knowledge and attitudes towards substance use reflects how well medical schools prepare them to address this problem in practice.…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent study of emergency physicians showed that only a minority routinely ask about illicit drug use, far fewer than ask about tobacco or alcohol use (Williams et al, 2000). Studies of primary and emergency physician attitudes toward substance-misuse screening indicate concerns about the sensitivity of the questions, inadequate training, and the time required and lack of reimbursement for this effort (Friedmann et al, 2001;Gentilello, 2005;Schermer et al, 2003;Yoast et al, 2008). Concerns regarding asking about or documenting an illegal practice also may deter physicians from asking about drug use, whereas similar concerns would not exist for questions about alcohol use, at least among adults age 21 and older.…”
Section: Llicit Drug Use Is Common In the United Statesmentioning
confidence: 99%
“…These negative attitudes and feelings of anger toward PWUS may deter women from disclosing their substance use. Personal bias and poor modeling by educators may cause students to question and blame pregnant women who endanger their fetuses by using drugs and alcohol [25][26]. Thus, PWUS may be unwilling to honestly report their substance use because they may be in denial, guilt or shame, fear of being stigmatized and judged, or dread consequences such as child apprehension or legal intervention [3].…”
Section: Gaps In Prenatal Screening For Substance Usementioning
confidence: 99%
“…Not only have referrals from healthcare providers amongst PWUS entering treatment stayed consistently low [29], patients may refuse to accept a referral or not keep their appointments. Also, most physicians lack adequate formal undergraduate and graduate training in the management of substance use during pregnancy [25,26,30]. Only 55% and 41% of physicians and pediatricians, respectively, reported feeling prepared to manage PWUS [20].…”
Section: Gaps In Prenatal Screening For Substance Usementioning
confidence: 99%